Analysis of Existential Feminism Struggle of Women Online Drivers During the Covid-19 Pandemic - Allen Pranata Putra; Erwan Aristyanto (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2021)
This article discusses the women's movement to sustain its existentialism in the COVID-19 pandemic by moving and taking high risks to become female online drivers. Based on research conducted by Simone De Beauvoir, who analyzed the film